2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7471774
|View full text |Cite
|
Sign up to set email alerts
|

Fast and efficient rejection of background waveforms in interictal EEG

Abstract: Automated annotation of electroencephalograms (EEG) of epileptic patients is important in diagnosis and management of epilepsy. Epilepsy is often associated with the presence of epileptiform transients (ET) in the EEG. To develop an efficient ET detector, a vast amount of data is required to train and evaluate the performance of the detector. Interictal EEG data contains mostly background waveforms, since ETs only occur occasionally in most patients. In order to detect ETs in an automated fashion, it is meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Some previous studies have applied nonlinear energy operator (NLEO) for IED detection purposes (Mukhopadhyay and Ray, 1998; Liu et al, 2013; Bagheri et al, 2016). The NLEO is computed as: φk{x[n]}=normalx2[n]x[nk]x[n+k],where the resolution parameter k (Choi and Kim, 2002) is chosen to have values in the range of 1–40.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have applied nonlinear energy operator (NLEO) for IED detection purposes (Mukhopadhyay and Ray, 1998; Liu et al, 2013; Bagheri et al, 2016). The NLEO is computed as: φk{x[n]}=normalx2[n]x[nk]x[n+k],where the resolution parameter k (Choi and Kim, 2002) is chosen to have values in the range of 1–40.…”
Section: Methodsmentioning
confidence: 99%
“…Many recent IED detection algorithms have applied wavelet analysis (Senhadji et al, 1995; Latka et al, 2003; Güler and Übeyli, 2005; Indiradevi et al, 2008; Bagheri et al, 2016). In this study, the discrete wavelet transform (DWT) was applied to decompose the signal into multiple scales based on wavelet basis functions.…”
Section: Methodsmentioning
confidence: 99%
“…Some methods have combined different techniques of classification as well as artifact removal methods [1013]. For instance, they have applied template matching combined with clustering [10], template matching combined with support vector machines (SVMs) and independent component analysis (ICA) [11], nonlinear energy operator combined with mimetic analysis and Adaboost classifiers [12], and sequence merging combined by SVMs [13], wavelet transform with machine learning techniques [14, 15]. In a recent study [16], the performance of an ET detection software on a dataset consisting of 40 epileptic patients, was compared with ET detection by three skilled technologists.…”
Section: Introductionmentioning
confidence: 99%
“…The background rejection system separated approximately 1% of the background waveforms, with less than 1% loss in sensitivity. The performance of the background rejection system is superior to the different methods suggested in the literature [131]. Later the extracted FP backgrounds were applied for improving the performance of the various IED detectors.…”
Section: Background Rejectionmentioning
confidence: 99%
“…After the rejection, sophisticated and highly accurate techniques are applied to the remaining miniature dataset. Bagheri et al has demonstrated the method of background rejection in [131]. The feature set consisted of morphological features, Non-Linear Energy Operator (NLEO) values, Discrete Wavelet Transform (DWT) coefficients, Continuous Wavelet Transform (CWT) coefficients, and frequency band features.…”
Section: Introductionmentioning
confidence: 99%